Comparative analysis of genomic sequence dependent and sequence-independent approaches to identify RNA editing sites in human primary monocytes / Leong Wai Mun - Leong , Wai Mun (2018)
RNA editing is an enzyme-mediated transcriptional alteration mechanism in eukaryotic cells that changes the sequences of primary RNA transcripts through nucleotide modification, insertion or deletion which leads to the diversification of gene products. Discovering RNA editing events in terms of frequency and location could provide useful information into their molecular adaptation as well as in determining their biological functions and regulation potentials at the cellular and organismic levels. The advancements of high-throughput sequencing technologies have resulted in the identification of significant numbers of RNA editing sites. Conventionally, both genomic and transcriptomic sequences are required for analysis. Recently, high-depth transcriptome sequencing approach (RNA-Seq) has enabled the identification of editing events without depending on the genomic sequences. In this study, both genomic sequence-dependent and genomic sequence-independent approaches were used to identify RNA editing sites present in human primary monocytes from a healthy individual. This will also allow comparative analysis being conducted on the reliability of both methods in discovering the editing sites. From the analysis, more editing events were detected using the genomic sequence-independent method (based on RNA sequences alone). Discrimination of RNA editing sites from genome-encoded single-nucleotide polymorphism (SNPs) is known to be one of the main challenges in identifying RNA editing sites. When we filtered the putative RNA editing sites identified through genome sequence-independent and sequence-dependent approaches with the Single Nucleotide Polymorphism Database (dbSNP), 71% and 10% of known SNPs were found, respectively. Hence, suggesting that DNA-Seq information from the same individual may possibly reduce the chances of novel and rare genomic variants (SNPs) being interpreted as RNA editing events. Furthermore, genomic localization and distribution of RNA editing sites in healthy human primary monocytes were profiled. The results obtained showed that majority of the editing sites resided in the non-coding regions. As far as we know, this is the first study that utilized both genomic-dependent and genomic-independent sequence approaches to identify RNA editing sites using high-depth genomic and transcriptomics datasets. The pipelines described in this study would certainly be useful for RNA editing sites identification in other human cells. Moreover, our findings will also serve as a reference for future functional study of specific editing events in healthy human primary monocytes as well as comparative study for disease-states human monocytes.